Acute Portal Vein Thrombosis - Thornburg, Bartley (Digestive Disease Interventions, 2017)
Acute portal vein thrombosis (PVT) is characterized by thrombus formation within the portal vein or its branches. This thrombus formation leads to a nonspecific clinical presentation, which emphasizes the need for imaging to establish the diagnosis. Prompt diagnosis is vital, because if left untreated, acute PVT can lead to bowel infarction or the clinical sequelae of portal hypertension. Currently, guidelines recommend anticoagulation as first line therapy for patients with acute PVT with endovascular management reserved for those who fail anticoagulation or present with signs of bowel ischemia. However, many patients treated with anticoagulation will develop portal vein cavernoma and long term sequalea of portal hypertension, which suggests the need for earlier endovascular intervention in select patients. This article will discuss the risk factors for development of acute PVT, the clinical presentation and diagnosis of the disease, and the pharmacologic, endovascular, and surgical therapy options.
Keywords: PVT; recanalization; thrombus